If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2x-11)/3=4/3+x
We simplify the equation to the form, which is simple to understand
(2x-11)/3=4/3+x
Simplifying:
(2x-11)/3=+1.33333333333+x
Reorder the terms in parentheses
( + 0.666666666667x-3.66666666667)=+1.33333333333+x
Remove unnecessary parentheses
+ 0.666666666667x-3.66666666667=+1.33333333333+x
We move all terms containing x to the left and all other terms to the right.
+ 0.666666666667x-1x=+1.33333333333+3.66666666667
We simplify left and right side of the equation.
-0.333333333333x=+5
We divide both sides of the equation by -0.333333333333 to get x.
x=-15
| 22/11x9-3^2 | | 5y=-6(0)-30 | | (x+2)/(x-3)=2 | | v=x(18-2x)(9-2x) | | 4x=-2(2x+4) | | x^2+8x+12y+4=0 | | (7xy)-(3xy)= | | 6m+7m=0 | | x(3x^2-5x-2)=0 | | 8+x=-31 | | 6(v+3)-2v=2(2v+3)-14 | | -3=-1/3h-10 | | 2/3x-12 | | 3-(x-4)=48 | | 18=x+3+2x | | 42/18 | | 15-3k=5(k-5)-3k | | (2/3)x-(1/6)=(2/7) | | d=85t+340 | | 3(3*x+4*y+5)+2(2*x-4*y-3)=z | | 2x=4x+18 | | 6-5(3x-2)=-14 | | X+.25X=45 | | 16x-5=2(2x+3) | | -149=10x-29 | | 4/(-1)-5 | | 6=(y-10) | | 4/(-1) | | (3x-2/4)+(x+57/7)=13 | | x4/x=2 | | 30=90/x | | (9-2y)/3=y |